PENGGUNAAN DIKSI PADA WACANA DISKUSI HAFLAH AKHIRUSSANAH SANTRI PONDOK PESANTREN DARUL ULUM MEDALI SUGIO LAMONGAN - Sadarus Aminun (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
Diction with the accuracy and appropriateness of word choices related to meaning, grammatical, social, and standard words. The purpose of this research is to be able to see the types of errors in the use of diction and its factors in the discussion discourse of the third and sixth grade santri end of the Islamic Boarding School Darul Ulum Medal Sugio Lamongan. This research uses descriptive qualitative type method. The data in this study are in the form of errors in using diction in the discussion. The techniques used in this research are observation, listening, and note-taking techniques. The results of this study are in the form of errors in the use of diction, including (a) inaccurate use of words, (b) using words in pairs, (c) using two words, (d) introducing between sentences and words, and (e) eliminating prepositions. These factors include (a) the lack of vocabulary, lack of knowledge of word processing and (c) lack of understanding of the language users' understanding of the meaning of the words they use.